Manzoni's annotations on Pierre de la Mésangère's 'Dictionnaire des proverbes français' (Prassi Ecdotiche della Modernità Letteraria, 2018)
This article aims at describing and commenting a selection of Manzoni’s marginalia to Pierre de la Mésangère’s Dictionnaire des proverbes français (1823). The typology of these marginalia can be defined linguistic since Manzoni, still relying on French and the Milanese dialect, tries, thanks to the Crusca Vocabulary as well, to find a proper Italian (or better, Tuscan) translation of the French proverbs. The annotation of the volume, despite being half done, proves to be a valuable evidence of Manzoni’s early awareness towards the most suitable linguistic elements for his novel: as a matter of fact, the comparison between these marginalia and the different drafts of the novel shows that many of the annotated proverbs are reused in the so-called Seconda minuta.
Keywords: Manzoni; Pierre de la Mésangère; Dictionnaire des proverbes français; notes; annotations